Qualitative aspects of differential equations in an inquiry-oriented course - Habre, Samer S. (2023)
In spring 2018, an inquiry-oriented differential equations course was offered at the Lebanese American University. This paper highlights students’ comprehension of some qualitative aspects of differential equations, namely their understanding of the equations and their solutions. It also explores the students’ success in moving between the qualitative and quantitative aspects of an equation. The analysis is based on questionnaire results and on students’ performances on problems that have been categorized as procedural versus non-procedural. Results show that the inquiry-based approach succeeded in having the students acquire a fair understanding of the qualitative aspect of the core concepts of the course. This came to be, however, not at the expense of the quantitative techniques that are usually emphasized in a traditional setting. The inquisitive nature of the course, even for recipe style concepts proved to be effective.